Deskripsi Sikap Kejujuran Dalam Hasil Belajar PPKn Siswa SMP Negeri 19 Kota Jambi - Dahliya, Iis; Usmanto, Heri; Sariani, Dona; Simaremare, Tohap Pandapotan (Civic Education Perspective Journal, 2021)
Abstract: The results of the study are the description of the honesty attitude of the eighth grade students of SMP Negeri 19 Jambi City can be said to be still low. Based on research findings from researcher interviews, not all students are able to apply the value of honesty in Civics learning. It can be seen from the daily tests that many students cheat, and when online, students do assignments and tests and tests at home, it is not necessarily the student who actually does it if it is reflected by the behavior of students at school before going online where when the teacher is off guard they cheat on each other. The conclusion of this study is that if you look at the learning outcomes, from online learning due to the covid-19 pandemic, student learning outcomes are still low, but after students do remedial, student scores can reach the KKM, and add the value of the assignment. However, if the test scores or exam results, on average, there are still many who are below the KKM. This is based on a clarification from a PPKn teacher at SMP Negeri 19 Jambi City. Because there are still many who are below the Minimum Completeness Criteria (KKM), so teachers need to add value from assignments, and teachers give tolerance to students, due to the Covid-19 pandemic obstacles that have not been completed during the class promotion exam.